(untitled) (Journal of the College of Basic Education, 2023)
Teaching physical education is serious and hard work, and the person who practices this profession needsTo a lot of time to learn the way in order to be qualified to teach. As it is knownThe learning process does not stop at one limit, but it is a continuous and evolving process with time. And to programThe preparation of teachers in universities provides the scientific foundations for the student through scientific lessons.Practical and applied, which he deals with during the years of study. But the basics of teaching began a long time agoThe day on which he is entrusted with the task of teaching a class or training a group of young people. And at thisPoint He will start by sorting out which scientific materials and information are useful to him and what are the skills that he needs.needed in his field of specialization. By observing the physical education lessons of manySchools and a study of many sources in this regard showed us that the methodPhysical education needs a lot of time and effort in order to reach the final goal.most of the education process.